MP48: White blood cells count and C-reactive protein performance to identify severe bacterial infection in the fever without a source workup of infants 22 to 60 days old. (May 2019) - Gravel, G.; Vachon, K.; Giguère, M.; Lajeunesse, L.; Morin, J.; Ouellet-Pelletier, J.; Turgeon, R.; Berthelot, S.
Abstract : Introduction : Identification of severe bacterial infections (SBI) among infants presenting to the emergency department (ED) for fever without a source (FWS) remains challenging. Controversies persist on the usefulness of blood biomarkers, especially when used for assessing infants 22 to 60 days old. Although C-reactive protein (CRP) and white blood cells count (leucocytes) are commonly prescribed, this practice relies on poor and conflicting evidence. Our objective was to determine the performance of those two markers at identifying SBI.Methods : This is a sub-analysis of an ongoing retrospective cohort study conducted in an academic pediatric ED in Quebec City, that aims to determine whether a lumbar puncture should routinely be performed in the FWS workup of 22 to 60 days old infants. All consecutive charts of eligible febrile infants were reviewed. Premature infants (<37 weeks), as well as infants with chronic diseases, immunodeficiency, previous antimicrobial therapy, in-dwelling catheters, or septic shock were excluded. Among others, data related to final diagnosis and investigations were gathered. Sensitivity, specificity, positive (PPV) and negative (NPV) predictive values, positive (LR+) and negative (LR-) likelihood ratios were estimated for each blood biomarkers.Results : Out of 1261 charts reviewed, 920 patients were included in this analysis. SBI prevalence was 13.0% (95%CI: 10.9-15.2) among infants of our cohort. The sensitivity, specificity, PPV, NPV, LR+ and LR- of the leucocytes <5000 or≥15000/□L were 43% (95%CI: 34-53%), 80% (95%CI: 77-83%), 25% (95%CI: 21-30%), 90% (95%CI: 88-91%), 2.1 (95%CI: 1.7-2.8), and 0.72 (95%CI: 0.61-0.84), respectively. The sensitivity, specificity, PPV and NPV of CRP >= 25 mg/L were 46% (95%CI: 37-56%), 96% (95%CI: 94-97%), 65% (95%CI: 55-73%), and 91% (95%CI: 89-92%), respectively. ROC curves analysis indicates that a CRP≥25 mg/L offers the best LR+ (10.4; 95%CI: 6.9-15.6) with a corresponding LR- of 0.56 (95%CI: 0.47-0.67).Conclusion : When evaluating febrile infants in the ED, leucocytes appear to have limited added value, while CRP≥25 mg/L significantly increases the pre-test probability of SBI. CRP should be considered for inclusion in the workup of FWS for infants of 22 to 60 days of age.